Evaluasi Isolat Pseudomonad fluoresens Indigenus dari Rizosfir Berbagai Kultivar Tanaman Pisang Sehat di Lahan Endemik Penyakit Layu Fusarium untuk Pengendalian Penyakit Layu Fusarium: english - Sulyanti, Eri; Habazar, Trimurti; Husin, Eti Farda; Nasir, Nasril; Dharma, Abdi (Jurnal Proteksi Tanaman (Journal of Plant Protection), 2018)
Fusarium wilt diseases caused by Fusarium oxysporum f sp cubense (Foc) is the most important diseases on banana in the world. Once Foc is present in the soil, it cannot be eliminated. The aim of research was to evaluate the potential of Pseudomonad fluorescens indigenous to control Fusarium wilt in planta. This experiment was arranged by completely randomized design with 17 treatments and 10 replications. Sixteen isolates of P. fluorescens indigenous had been successly taken from several different cultivars of banana rhizospheres at endemic area of Fusarium wilt in the centre of banana production in West Sumatra that were introduced to banana seedlings cv Cavendish inoculated with Foc. The variable observed were incubation period, percentage of leaf infection, discoloration of pseudostem and the intensity of damaged corms. The result showed that The PfCvP1 isolate (from rhizosphere of Cavendish at low altitude area) was the most effective to inhibit the development of Fusarium wilt: 97.89 % (prolong incubation period), 67.26 % (reduced infected leaves), 63.63 % (reduced damaged corm), and 72.62 % (reduced disclorotion of pseudostem) and increased plant growth.